DIAGNOSTICS OF PROSTATE CANCER: A 10 YEARS SYSTEMATIC REVIEW - Ramadhani, Rizkia Amal; Fithri Rofifa, Amira (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background:  Prostate cancer ranks as the second most common malignancy in men globally, following lung cancer. The present method of diagnosing prostate cancer is marked by a significant level of diagnostic uncertainty. This uncertainty has led to both overtreating and undertreating, leaving the medical community unsure about the most effective approach for prostate cancer diagnosis. This study aims to to provide a 10 year systematic review of prostate cancer diagnosis. Methods: This systematic review adhered to the PRISMA 2020 standards and included full-text English literature published between 2014 and 2024. Exclusion criteria involved editorials, review articles from the same journal, and submissions lacking a DOI. Literature was gathered from online sources such as PubMed and SagePub. Result: Our search in PubMed yielded 24,278 articles, while SagePub produced 5,016 articles. Focusing on the year 2014, PubMed had 270 articles, and SagePub had 502. Ultimately  we selected 5 papers that met our criteria, 3 from PubMed and 2 from SagePub. Conclusion:  This study concludes that prostate cancer diagnosis can be done with biopsy in combinations to other modalities such as vibrational spectroscopy, PSA level and PSA-density, mpMRI, and biomarkers such as PCA3 and AMACR.